Quali-quantitative analysis of the phenolic fraction of the flowers of Corylus avellana, source of the Italian PGI product "Nocciola di Giffoni": Isolation of antioxidant diarylheptanoids. (October 2016) - Masullo, Milena; Mari, Angela; Cerulli, Antonietta; Bottone, Alfredo; Kontek, Bogdan; Olas, Beata; Pizza, Cosimo; Piacente, Sonia
Abstract: There is only limited information available on the chemical composition of the non-edible parts of Corylus avellana, source of the Italian PGI product "Nocciola di Giffoni" (hazelnut). An initial LC-MS profile of the methanolic extract of the male flowers of C. avellana, cultivar 'Tonda di Giffoni' led to the isolation of 12 compounds, of which the structures were elucidated by NMR spectroscopy. These were identified as three previously undescribed diarylheptanoids, named giffonins Q-S, along with nine known compounds. Furthermore, the quantitative determination of the main compounds occurring in the methanolic extract of C. avellana flowers was carried out by an analytical approach based on LC-ESI(QqQ)MS, using the Multiple Reaction Monitoring (MRM) experiment. In order to explore the antioxidant ability of C. avellana flowers, the methanolic extract and the isolated compounds were evaluated for their inhibitory effects on human plasma lipid peroxidation induced by H2 O2 and H2 O2 /Fe 2+, by measuring the concentration of TBARS. Graphical abstract: Three diarylheptanoids named giffonins Q-S (10–12 ) along with nine known compounds were isolated from the MeOH extract of the flowers of Corylusavellana, cultivar 'Tonda di Giffoni'. The quantitative determination of the main compounds and the evaluation of their inhibitory effects on human plasma lipid peroxidation induced by H2 O2 and H2 O2 /Fe 2+ were carried out. Highlights: A LC-MS profile of the MeOH extract of the flowers of C. avellana, cultivar 'Tonda di Giffoni', was carried out. Three diarylheptanoids never reported before along with nine known flavonoid derivatives were isolated. A LC-ESI(QqQ)MS method for quantitative analysis of the main compounds was developed. The MeOH extract and most of the isolated compounds showed promising activity in the TBARS assay.